PERAN FORUM KERUKUNAN UMAT BERAGAMA (FKUB) DALAM MENJAGA KERUKUNAN UMAT BERAGAMA DI KOTA BUKITTINGGI - Lubis, Bahran Efendi (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The City of Bukittinggi is a multiethnic and multireligious city, the life of the religious community in this city is generally conducive, meaning that there has never been a violent conflict, but actually has latent conflicts between religious groups because of differences in interests. Religious cases and social cases religious nuances that have accurred so far whether actual or not, prove that the latent conflict among religious communities is quite intense. This research wants to ding deeper into the condition of the diversity and harmony among religious communities in the city of Bukittinggi. This research is a descriptive qualitative research. The results of this study include: The general city of Bukittinggi has a fairly conducive condition, but has latent conflict between religious grups due to diffrences in interests and lack of intensive communication. The internal religious harmony in the city of Bukittinggi is quite good. The harmony between religious communities in the city of Bukittunggi seems to still have conflicts between religious, this is due to a lack of cooperation. The harmony of the religious community with the government in the city of Bukittinggi seems quite good. FKUB of Bukittinggi city has carried out its role in accordance with the duties of FKUB in PBM No. 9 and 8 of 2006.